2015
DOI: 10.1109/tap.2015.2412147
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Spatio-Temporal Radio Channel Model for Large Indoor Environments at 60 and 70 GHz

Abstract: Millimeter-wave radios operating at unlicensed 60 GHz and licensed 70 GHz bands are attractive solutions to realize short-range backhaul links for flexible wireless network deployment. We present a measurement-based spatio-temporal statistical channel model for short-range millimeter-wave links in large office rooms, shopping mall, and station scenarios. Channel sounding in these scenarios at 60 and 70 GHz revealed that spatio-temporal channel characteristics of the two frequencies are similar, making it possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 14 publications
2
94
0
Order By: Relevance
“…Following the approach described in [13], [18], extended to the double-directional channel, the synthetic omnidirectional power delay profile (PDP) is then obtained as follows:…”
Section: Multipath Detection Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the approach described in [13], [18], extended to the double-directional channel, the synthetic omnidirectional power delay profile (PDP) is then obtained as follows:…”
Section: Multipath Detection Algorithmmentioning
confidence: 99%
“…Rx). The number of detectable paths (N k ) and their corresponding delays τ k , (k = {1...N k }) is determined from the synthetic P DP p (τ ) by applying the path detection algorithm defined in [13]. The algorithm searches for local maxima in the synthetic omnidirectional PDP by comparison with the threshold function defined as:…”
Section: Multipath Detection Algorithmmentioning
confidence: 99%
“…[88] complements the cluster parameters following the principle of the 11ad-model, and furthermore found that small fixtures such as ceiling lamps and shelfs are often visible as clusters, despite they are neglected for the sake of simplicity in the 11ad-model. As an alternative model, the papers [89], [90] characterize their measured PDPs as a combination of specular and diffuse components that appear as discrete spikes and continuously decaying power spectrum over delay, respectively. The diffuse spectrum behaves as if it was a noise floor, as commonly observed in PDPs at microwave frequencies [91].…”
Section: Power Delay Profilesmentioning
confidence: 99%
“…In contrast, there are also works reporting PAS spread over wide angular range; [71] shows PAS of outdoor rooftop-to-ground channels at 28 GHz, revealing rich scattering even in LOS cases. The work [90] reports that radio channels in large indoor scenarios at 60 and 70 GHz show a uniform distribution of propagation paths over the azimuth angle, and that the path clustering phenomenon is not prevailing over the spatio-temporal domain.…”
Section: Power Delay Profilesmentioning
confidence: 99%
See 1 more Smart Citation